Corpus of knowledge in the ranches of La Soledad, Baja California Sur: Transfers for initial teacher training - Piñeda Verdugo, Tito Fernando; Carballo Lucero, Arcelia; Lira Beltrán, Andrea Maricela (IE Revista de Investigación Educativa de la REDIECH, 2024)
The European modernity ideologically influenced those who promoted the establishment of teacher training schools in Mexico. The teaching framework, influenced by positivism, excluded the traditional knowledge of rural and indigenous communities, considering it an obstacle to the country’s cultural progress. After nearly two centuries of normalista history, recent educational reforms suggest the need to train teachers who can revalue this knowledge, aiming to develop territorially grounded learning. To address these new training needs for teaching staff and to have firsthand information for designing flexible curriculum courses for Geography and Biology teaching and learning degrees at the Escuela Normal Superior de Baja California Sur, an ethnoecological study was conducted in the ranching territory of La Soledad, in the Baja California peninsula. This study examined the sociocognitive relationships that original peasant societies in the region establish with their environments, identifying local knowledge about 63 plants with productive, medicinal, and food uses. The research facilitated the organization of a corpus of traditional and ecological ranching knowledge, which upon analysis, allowed for the historical, geographical, and biocultural contextualization of the design of five courses now integrated into the 2022 curriculum.